MATHEMATICAL MODELING OF VERTICAL STRATIFICATION OF LANDSCAPES (Scientific journal of the Fergana State University, 2024)
In the article, the importance of landscapes in the development of the economy and the issues of ecological optimization through mathematical modeling in the effective use of landscapes in the Fergana Valley are highlighted. Also, numerical values related to the mathematical model of the Fergana Valley for the years 1997, 2010, and 2011 were shown. In addition, it is necessary to develop a comprehensive multidisciplinary approach to the functional, correlational, ecological, and economic orientation of the changing landscape types.